The influence of moderate physical activities on the psychophysical state of children with minimal brain dysfunctions - Hrytsiuk, Iryna; Koshyrets, Viktor; Khvorost, Khrystyna; Mushkevych, Myroslava; Duchiminska, Tamara; Mahdysiuk, Liudmyla; Fenyna, Oksana (University of Pitesti, 2018)
Recently in Ukraine the number of children with deviations in psychological development has been increasing. Children with minimal brain dysfunction have motion disorders in the form of deviations of fine motor hand skills, coordination of motions, balance, and speech. Few studies are available on children’s minimal brain dysfunction and its correlation with physical activity. The purpose of the present paper is to reorganize emotional, volitional, behavioral and other adaptive manifestations of children with minimal brain dysfunction by means of moderate physical activities. Firstly, the research is focused on the creation of safe stimulating environment where children are faced with moderate physical challenges. All of them are aimed at motor skills development and gradual child’s involvement into different activities. As a result, it stimulates brain growth. Secondly, an analysis is given of parents’ applications, bringing up children, characterized by increased levels of excitability; have neurological symptoms (increased fatigue, speech disorders); demonstrate behavioral and learning difficulties; as well as children with psycho-neurological diagnosis, appointed in different periods of their ontogenesis. These children were integrated by one indicator - minimal brain dysfunction. Thirdly, in the process of forming the experiment we actively modeled a social profile of children with minimal brain dysfunction by means of psychocorrection and psychotherapy (using moderate physical activity). Hence, having carried out the empirical statement of psyche, we acquired positive changes in different psyche manifestations of these children. In particular, social and behavioral competences improved, changes of intellectual and psychomotor abilities took place. Thus, children with impaired brain structures maturation require correction. Among the most influential are increasing otivation to learn; organization of educational process considering children’s psychophysiological peculiarities; development of deficiency functions, as well as development of constructive norms of interaction with adults and peers. Important components that can help with this are various forms of play activity that include moderate physical activity.
Keywords: minimal brain dysfunctions; stages of personality development; psychophysiological functions; disharmonious development; moderate physical activity; psychological correctional work